Implementation of a Pharmacist-Administered Influenza Vaccination Program in the Oupatient Setting at the Military Treatment Facility - Sean O'Brien; Jennifer Bellisario (University of Minnesota Libraries Publishing, 2018)
The goal of the Army's influenza prevention program is to protect all Soldiers, healthcare professionals, and beneficiaries from influenza and its complications to maximize force readiness.  Commanders have the daunting and challenging task of ensuring 100% of Soldiers and Military Treatment Facility (MTF) assigned employees are vaccinated against influenza by a specified timeframe.  Outpatient Pharmacy Services at the MTF are in the perfect position to provide enhanced accessibility to the influenza vaccination to assist in meeting this requirement.  Irwin Army Community Hospital at Fort Riley, Kansas, became the first MTF to offer a pharmacist-administered influenza vaccination program in the outpatient setting, as a walk-in service to all Soldiers, MTF employees, and beneficiaries, in 2016. Since then over 1,500 flu shots have been administered with no documented adverse events, and a potential cost-savings between $23,205 to $61,880.  Here we describe the planning and implementation of such a program, which can easily be reproduced at any MTF outpatient pharmacy with minimal efforts and resources, enabling outpatient pharmacists to provide a convenient and accessible alternative for seasonal flu vaccination, with the ultimate goal of maximizing force readiness. Article Type: Idea Paper